A Study of Performance of the KLSE Syariah Index (Malaysian Management Journal, 2002)
This study compares the performance of the Syariah Index (SI) and the Composite Index (CI) of the Kuala Lumpur Stock Exchange (KLSE) during the period April 1 999 to January 2002, Both the raw and risk-adjusted returns were calculated for the indices for the whole and two sub-periods. Results based on the raw returns revealed that generally, the KLSE SI and CI recorded the same level of returns. Tests using performance measures of Adjusted Sharpe Index, Treynor Index and Adjusted Jensen Alpha revealed that there were also no significant difference in the (risk-adjusted) performance of both indices. We therefore conclude that Syariah-approved stocks were not more favourable than the other stocks in the KLSE.